The Application of The Pancasila Profile in The Skill Aspect at SDN Tayem East 3 - Amalia Nurul Azizah; Alwi Sofyan (Universitas Sebelas Maret, 2022)
This study aims to analyze the application of the Pancasila profile in the aspect of skills at SDN Tayem Timur 3. The method used is a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The research subjects were school principals, teachers, and students of grades V and VI. The results of the study show that the application of the Pancasila profile in the skills aspect at SDN Tayem Timur 3 is quite good, as can be seen from the development of student’s skills in various aspects such as critical thinking, creativity, and communication skills. In addition, the application of the Pancasila profile also helps increase student awareness of Pancasila values as a guide in everyday life. However, more efforts are still needed to improve the quality of the application of the Pancasila profile in the skills aspect, such as by providing training and guidance to teachers and students.